Satisfaction levels of elite track and field athletes in South Korea - Park, Y. J.; DeSchriver, D.; Bestman, L.; Lim, J. (The Sport Journal, 1999)
The general problem of this study was to examine the level of satisfaction of elite track and field athletes in South Korea with six factors; facilities, equipment, financial support, head coach's technical ability, training methods, and leadership.